Metastatic Choriocarcinoma Following Live Birth A Rare Presentation - Roy, Joya Sree; Wasik, Sadia; Begum, Afrina; Hossen, Md Murraf; Hossain, Farhat (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Choriocarcinoma is the most malignant tumor of gestational trophoblastic neoplasia. Post-partum choriocarcinoma is an infrequent event with poor prognosis. The diagnosis is usually delayed due to failure to recognize the mode of presentation of this disease. Being a rare occurrence, limited data is available regarding its clinical features. We present a 24 years old women with parity one delivered by caesarean section indicated for premature rupture of membrane with fetal distress at 39 wks of pregnancy. Frequent episodes of heavy vaginal bleeding had started 28 days following C/S. For this, she had H/O uterine evacuatin twice within 5 days interval. Biopsy report of second curettage showed choriocarcinoma. On admission to Dhaka Medical College Hospital (DMCH), the pretreatment Human Chorionic Gonadotrophin (βhCG) level was >200000.0 IU/L, uterine mass of about 18 wks pregnancy size & X-Ray chest showed segmental consolidation in left mid zone of lung. After consultation with oncologist Etoposide, Methotrexate, Dactinomycin, Cyclophosphamide & Vincristine (EMACO) therapy was started but before completion of her proposed cycles, she developed a live threatening condition which was managed very urgently and meticulously. Now the patient is under regular monitoring. Key words: GTD; Choriocarcinoma DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8642 BSMMU J 2011; 4(2):116-118